Logic and Philosophy of Religion - Silvestre, Ricardo Sousa (Sophia, 2017)
This paper introduces a special issue on logic and philosophy of religion in this journal (Sophia). After discussing the role played by logic in the philosophy of religion along with classical developments, we present the basic motivation for this special issue accompanied by an exposition of its content.